Editorial: Knowledge production - El Director (2015)
Societies that did not take this assertion into account, vegetate today within precarious productivist schemes and erratic cultural formats. Any country that has not made knowledge the basis for its development is condemned to dependency and underdevelopment. Therefore, the production of knowledge, based on research and experimental development, should be the most valuable area in the management of our university and our faculty.